Why do they not want to go back home? A perspective of African graduates in the United States - Rukema, Joseph Rudigi; Nkoko, Mosa (Dhaulagiri Journal of Sociology and Anthropology, 2024)
This study aims to explore and examine why some African graduates decide to remain in the United States after completing their studies, when they stand a good chance to secure better job opportunities when returning to their home countries because of quality education in the US. The experience of African graduates after deciding to remain in the US is also examined in this study. This is a qualitative study using an exploratory approach, through a snowball sampling method. In order to achieve its objectives, interviews were conducted through the use of social media platforms with 15 graduates from Kenya and Nigeria living in the US. The findings have that shown quality education in the US as well as its economic and political stability were the pull factors for graduates to remain in the US after completing their studies. The findings have also shown that while graduates stand a better chance to access good employment opportunities when they return home, they expressed concerns about high levels of nepotism, corruption in the employment process, and lack of infrastructure. Examining the experience of graduates after deciding to remain in the US, loneliness, lack of social support and perceived racism were among some of the experiences of African graduates in the US.